Analisis Parameter Pemesinan pada Proses Side Milling Baja AISI 1045 Menggunakan Response Surface Methodology (RSM) - Arif Afriansyah; Muhammad Yanis (Universitas Sriwijaya, 2021)
Surface roughness is one of the criteria for determining machining quality. This parameter is influenced by machining parameters such as cutting speed (Vc), motion feed (fz) and radial depth of cut (ar). The material is processed using side milling with down milling feeding direction. The results of the milling process are measured with a surface roughness tester by taking the roughness arithmetic (Ra) value as the roughness value. Surface roughness prediction is done using response surface methodology (RSM). RSM was chosen as a quantitative approach based on experimental and modeling data. The number of data retrieval in this study were 16 experimental data for 3 machining parameters. Surface roughness modeling of AISI 1045 milling by Quadratic response surface methodology showed significant model results. Evidenced by the F-Value of 5.61 and P-Value of 0.0241. P-Value was <0.05 means that the model is significant. The mean square error mean in this study also showed good results in the amount of 0.0091 and an average error of 0.122%. The effect of cutting speed on roughness is the higher the cutting speed will produce a smooth roughness value, while the effect of feeding motion and feeding depth on roughness is directly proportional, the higher the value of feeding motion and the depth of feeding, the coarser the roughness score will be.